Identification of Crucial Genes and Infiltrating Immune Cells Underlying Sepsis-Induced Cardiomyopathy via Weighted Gene Co-Expression Network Analysis - Li, Juexing; Zhou, Lei; Li, Zhenhua; Yang, Shangneng; Tang, Liangyue; Gong, Hui (Frontiers in Genetics, 2021)
Sepsis-induced cardiomyopathy (SIC), with a possibly reversible cardiac dysfunction, is a potential complication of septic shock. Despite quite a few mechanisms including the inflammatory mediator, exosomes, mitochondrial dysfunction, etc., having been confirmed in the existing researches, we still find it obscurity about the overall situation of gene co-expression that how they can affect the pathological process of SIC. Thus, we intended to find out the crucial hub genes, biological signaling pathways, and infiltration of immunocytes underlying SIC. It was weighted gene co-expression network analysis that worked as our major method on the ground of the gene expression profiles: hearts of those who died from sepsis compared to hearts donated by non-failing humans which could not be transplanted for technical reasons (GSE79962). The top 25 percent of variant genes were abstracted to identify 10 co-expression modules. In these modules, brown and green modules showed the strongest negative and positive correlation with SIC, which were primarily enriched in bioenergy metabolism, immunoreaction, and cell death. Next, 9 genes (LRRC39, COQ10A, FSD2, PPP1R3A, TNFRSF11B, IL1RAP, DGKD, POR, THBS1) including 2 down- and 7 up-regulated genes were chosen as hub genes that meant the expressive level of which was higher than the counterparts in control groups. Then, the gene set enrichment analysis (GSEA) demonstrated a close relationship of hub genes to cardiac metabolism and the necroptosis and apoptosis of cells in SIC. Concerning immune cells infiltration, a higher level of neutrophils, B cells native, and a lower level of mast cells resting and plasma cells had been observed in patients with SIC. In general, 9 candidate biomarkers were authenticated as a reliable signature for deeper exploration of basic and clinical researches on SIC.